Discontinuity check of scanning in coordinate metrology. (January 2015) - Wozniak, Adam; Mayer, J.R.R.
Highlights: A new algorithm for discontinuity check of CMM scanning measurements is proposed. The method renders possible for users to evaluate the correctness of measurements. The validity of the algorithm is experimentally confirmed on a CMM. Abstract: The paper presents a new algorithm for detecting the presence of measurement discontinuities in scanning measurements carried out on coordinate measuring machines (CMMs). The proposed algorithm marks the regions that are inaccessible to the stylus tip. This allows the machine user to decide whether to change the tip for a smaller one. The method is for use in a high-definition coordinate metrology (HDCM) context, where the density of points per scanned distance ensures that the successive probe ball positions overlap partially with each other and can be applied directly to the data collected during a measuring process. The paper describes the operating principle of the new algorithm and experimental verification on a Zeiss ACCURA CMM with an active VAST Gold scanning probe.